Hubungan Aktivitas Mengikuti Kegiatan Musyawarah Guru Mata Pelajaran dengan Kinerja Guru Bidang Studi Agama di Madrasah Aliyah Negeri 1 Pekanbaru - Emilda, Tika; Yera Putri Rahayu; Darini, Rahma (Bedelau: Journal of Education and Learning, 2022)
This research is motivated by the demand for every teacher to display high performance in the teaching and learning process. Teachers are said to have high performance if the learning objectives achieved are in accordance with predetermined standards. One factor that can improve teacher performance is by participating in subject teacher deliberation activities, which are forums for teachers in certain subject areas to deliberate, exchange ideas and information so as to find appropriate learning alternatives to improve the quality of learning and in order to improve teacher performance. The problem formulation in this research is: a) What are the teacher's activities in participating in Subject Teacher Conference activities? b) How is the performance of teachers in the field of religious studies at Madrasah Aliyah Negeri 1 Pekanbaru? The research sample was nine teachers in the field of religious studies. The technique used in collecting data for both variables is through observation and documentation. After the data was collected, it was then analyzed descriptively qualitatively with percentages to determine the activities taking part in subject teacher deliberation activities and the performance of teachers in the field of religious studies. Meanwhile, to determine whether there is a relationship between the two variables, the data was analyzed statistically using the product moment correlation technique. Then the data is processed using computer equipment via the SPSS 16.0 for Windows program. Based on data analysis, the following results were obtained: 1) Teacher activity in participating in subject teacher deliberations was relatively high with a percentage of 78.02%. 2) The performance of teachers in the field of religious studies is relatively high with a percentage of 78.84%. The results of the correlation analysis of the two variables obtained rxy = 0.642. From the results of the correlation analysis, it can be seen that the relationship between the two variables is in the medium category. Conclusion of hypothesis testing rxy = 0.642 > 0.381 (5%) and 0.487 (1%). Thus Ha is accepted and Ho is rejected.